The methodology of the Agile Nudge University - Mehta, Jade; Williams, Christopher; Holden, Richard J.; Taylor, Britain; Fowler, Nicole R.; Boustani, Malaz (Frontiers in Health Services, 2023)
Introduction The Agile Nudge University is a National Institute on Aging-funded initiative to engineer a diverse, interdisciplinary network of scientists trained in Agile processes. Methods Members of the network are trained and mentored in rapid, iterative, and adaptive problem-solving techniques to develop, implement, and disseminate evidence-based nudges capable of addressing health disparities and improving the care of people living with Alzheimer's disease and other related dementias (ADRD). Results Each Agile Nudge University cohort completes a year-long online program, biweekly coaching and mentoring sessions, monthly group-based problem-solving sessions, and receives access to a five-day Bootcamp and the Agile Nudge Resource Library. Discussion The Agile Nudge University is evaluated through participant feedback, competency surveys, and tracking of the funding, research awards, and promotions of participating scholars. The Agile Nudge University is compounding national innovation efforts in overcoming the gaps in the ADRD discovery-to-delivery translational cycle.